PERANCANGAN ANIMASI INTERAKTIF TATA CARA PELAKSANAAN WUDHU DAN SHOLAT WAJIB - Sandra Jamu Kuryanti (Jurnal Khatulistiwa Informatika, 2015)
Animation is moving pictures formed from group of objects ( picture ) that arranged in regular either subscribe to the movement of as specified in every addition the ordinal of time which occurs .Design interactive animations procedures for ablution and compulsory prayers is made as a medium learning for students and the student to study procedures for ablution and compulsory prayers well and correctly .To the learning process by the use of this animation here will be very interesting the attention given to students because learning so it is not boring .In the design interactive animations uses the method this primary and secondary in data collection .Primary method where done by means of the spread of kuisioner to respondents , while the primary data that is data that has been collected the other hand .While a method of secondary done obtained by means of research literature available , read books are pertinent to the matter analyzed.Keyword: Animation ,multimedia, ablution, prayers